2022
DOI: 10.3390/su141710738
|View full text |Cite
|
Sign up to set email alerts
|

Productive Livestock Characterization and Recommendations for Good Practices Focused on the Achievement of the SDGs in the Ecuadorian Amazon

Abstract: The increase in livestock production in the Ecuadorian Amazon Region has caused an increase in deforestation and the advance of the agricultural frontier. The aim of the current study was to conduct a socioeconomic and productive characterization in Andean-Amazonian livestock systems in Ecuador. The study area was part of the Sumaco Biosphere Reserve (SBR) and three other zones: low (400 to 700 masl), middle (701 to 1600 masl), and high (701 to 1600 masl). Data were collected from 167 ranching households. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…The RA, despite its higher biodiversity, has shown an intense change due to the accelerated rate of deforestation, migration, and exploitation of oil [ 49 ]. In Ecuador, Torres et al [ 50 ] observed that small livestock farmers annually destinate big forest surfaces for conversion on pastures. Contrary to this result, in Orellana, despite type 1, there was more forest extension than in other typologies; however, this group showed an increase in deforestation rate and an advance of the agricultural frontier.…”
Section: Discussionmentioning
confidence: 99%
“…The RA, despite its higher biodiversity, has shown an intense change due to the accelerated rate of deforestation, migration, and exploitation of oil [ 49 ]. In Ecuador, Torres et al [ 50 ] observed that small livestock farmers annually destinate big forest surfaces for conversion on pastures. Contrary to this result, in Orellana, despite type 1, there was more forest extension than in other typologies; however, this group showed an increase in deforestation rate and an advance of the agricultural frontier.…”
Section: Discussionmentioning
confidence: 99%
“…Ecuador suffers the highest deforestation rate in South America, especially in the buffer zones around protected areas, where pastures are one of the most important drivers of deforestation [ 64 ]. The demand for meat and milk from a growing population has caused a rapid and uncontrolled expansion of livestock into natural areas, especially in poor communities where livestock operations are small but have a high impact on their economy [ 13 ]. These pastures, often further from households, are less guarded, and fencing or herding livestock during vulnerable times may be too costly for owners, making them more susceptible to predation events [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing concern about the socio-economic impact of free-ranging dog attacks on livestock, as they may be the main cause of animal loss for small farms, posing a threat to the livelihoods of vulnerable groups [ 9 , 10 , 11 ]. In addition, small-scale livestock production plays a fundamental role as a source of income and nutrition for households in developing countries like Ecuador [ 12 , 13 ]. Therefore, the presence of uncontrolled free-ranging dogs can have a negative impact on biodiversity conservation, public health, the economy, and food supply, 4 of the 17 Sustainable Development Goals (SDGs) created by the United Nations “to achieve a better and more sustainable future for all” [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average age of the dairy farmers was 48.22 years (Table 2), while the small-scale dairy farmers adjacent to Chimborazo Fauna Reserve (RPFC) in Ecuador are 5.32 years younger [37]. In the Sumaco Biosphere Reserve of the Ecuadorian Amazon, the farmers are 8.18 years older [38] and in the central Andes of Peru (Province of Pasco), they are 1.68 years older [39]. Regarding gender, there are 60.66% more men than women as heads of households in livestock systems, which could generate a nutritional imbalance of household members, since it has been shown that when women are heads of households, there is a significantly greater positive effect on child nutrition and household food security [40].…”
Section: Characterization Of Dairy Farmers' Livelihoods Using Capital...mentioning
confidence: 99%